Effective and Efficient Dispute Resolution Through Optimation of Court Connected Mediation - Indriati Amarini; Noorfajri Ismail; Ratna Kartika Wati; Marsitiningsih Marsitiningsih; Ika Ariani Kartini (UM Purwokerto Press, 2023)
The judiciary is a mechanism provided by the state to resolve disputes. However in practice, dispute resolution in court is not in accordance with the principles of justice, namely effective and efficient judicial institutions. This research aims to analyze the legality and development of mediation in court. The research method used is library research with secondary data sources in the form of laws and regulations, research results and literature. One of the progressive ideas of the Supreme Court of the Republic of Indonesia in order to realize effective and efficient courts, among others, is to strengthen the institution of mediation in the Court for the settlement of civil disputes. However, it seems that the efforts of the Supreme Court institutions need to be further refined through improving the quality and quantity of human resources, improving supporting infrastructure and court institutions are consistent in supporting the mediation development programs in the Court.